Host and parasite thermal acclimation responses depend on the stage of infection. (4th April 2016) - Altman, Karie A.; Paull, Sara H.; Johnson, Pieter T. J.; Golembieski, Michelle N.; Stephens, Jeffrey P.; LaFonte, Bryan E.; Raffel, Thomas R.
Summary: Global climate change is expected to alter patterns of temperature variability, which could influence species interactions including parasitism. Species interactions can be difficult to predict in variable‐temperature environments because of thermal acclimation responses, i.e. physiological changes that allow organisms to adjust to a new temperature following a temperature shift. The goal of this study was to determine how thermal acclimation influences host resistance to infection and to test for parasite acclimation responses, which might differ from host responses in important ways. We tested predictions of three, non‐mutually exclusive hypotheses regarding thermal acclimation effects on infection of green frog tadpoles ( Lithobates clamitans ) by the trematode parasite Ribeiroia ondatrae with fully replicated controlled‐temperature experiments. Trematodes or tadpoles were independently acclimated to a range of 'acclimation temperatures' prior to shifting them to new 'performance temperatures' for experimental infections. Trematodes that were acclimated to intermediate temperatures (19–22 °C) had greater encystment success across temperatures than either cold‐ or warm‐acclimated trematodes. However, host acclimation responses varied depending on the stage of infection (encystment vs. clearance): warm‐ (22–28 °C) and cold‐acclimated (13–19 °C) tadpoles had fewer parasites encyst at warm and cold performance temperatures, respectively, whereas intermediate‐acclimated tadpoles (19–25 °C) cleared the greatest proportion of parasites in the week following exposure. These results suggest that tadpoles use different immune mechanisms to resist different stages of trematode infection, and that each set of mechanisms has unique responses to temperature variability. Our results highlight the importance of considering thermal responses of both parasites and hosts when predicting disease patterns in variable‐temperature environments. Abstract : Temperature variability can have complex effects on parasitism, particularly if hosts and parasites acclimate to new temperatures. The authors used replicated temperature experiments to demonstrate nonlinear thermal acclimation responses in the trematode parasite Ribeiroia ondatrae and its tadpole host Lithobates clamitans . They tracked parasite encystment and clearance using fluorescent dye.